SOURCES OF AGROBIOLOGICAL TRAITS FOR BREEDING SPRING BARLEY VARIETIES IN THE NORTH-WEST OF THE RUSSIAN FEDERATION - N. V. Ivanova; A. V. Anisimova; T. N. Radyukevich; O. N. Kovaleva (Труды по прикладной ботанике, генетике и селекции, 2018)
A collection of spring barley accessions was studied according to such traits as the length of the growing season, the height of the straw, resistance to lodging and fungal diseases (net blotch and dark brown spot blotch, powdery mildew, stem rust, loose smut). Sources of valuable traits for breeding were identified. Varieties sensitive to some fungal diseases were marked out.